A comparative analysis of the accuracy of cardiac surgery risk scores in tricuspid valve procedures undertaken in the Republic of Georgia - Kumar, Yash Sailesh; Surve, Nameera Zaheer; Gelasvili, Daviti; Mamisashvili, Mariam; Jorbenadze, Mariami; Vashakidze, Nika (International Surgery Journal, 2024)
Background: Tricuspid valve (TV) surgeries present significant challenges marked by elevated risk and mortality rates. Despite the application of established risk scores like ACEF-II, EuroSCORE-II, and Hannan EL et al's risk stratification (HRS), their accuracy in predicting mortality rates for these procedures in a third-world setting remains under-researched. This study sought to assess the predictive performance and overall accuracy of these risk scores in the context of TV surgeries performed in the Republic of Georgia. Methods: A cohort of 63 patients who underwent TV procedures was retrospectively analyzed. ACEF-II, EuroSCORE-II, and HRS were applied and run through statistical analysis to assess their predictive capabilities. Results: ACEF-II demonstrated an accuracy rate of 58.7%, an area under the curve (AUC) of 0.819, and an expected-to-observed mortality ratio of 0.16. EuroSCORE-II exhibited an accuracy rate of 61.9%, an AUC of 0.866, and an expected-to-observed mortality ratio of 0.17. The HRS demonstrated an accuracy rate of 65.1%, an AUC of 0.882, and an expected-to-observed mortality ratio of 0.35. Conclusion: While the risk scores show promise, our study highlights their limitations in accurately predicting mortality rates of TV surgeries by underestimating them and emphasizes the need for refinement or the development of risk scores tailored specifically to TV procedures in third-world countries.